Caracterização funcional de genes relacionados à biorremediação em bactérias de estações de tratamento de esgoto - Araújo, Laura Rodrigues (2019)
Contamination of water bodies, mainly due to inadequate discharge of effluents, is one of the most impacting anthropogenic activities to the environment, causing sanitary, economic, and social problems. Therefore, it is necessary to understand the biological processes that occur in the wastewater treatment plants that allow the bioremediation of these wastes. Bacteria are the most present microorganisms in these environments, promoting the removal and/or degradation of organic matter and various nutrients like nitrogen, phosphorus, and sulfur. In this work, the main bacterial species present in different sewage treatment plants were identified and, by genomic analysis, which of these bacteria have the genes of degradation or absorption pathways of nitrogen, sulfur and phosphorus compounds. The genomes of 158 bacteria species, isolated from sewage treatment plants, were analyzed in search of the following pathways: nitrification, denitrification, dissimilatory nitrate reduction, phosphorus accumulation, assimilatory sulfate reduction, and dissimilatory sulfate reduction and oxidation. Seventy-nine bacteria species had at least one of the complete pathways, of which 11 had 3 or more complete pathways: Acidovorax caeni, Acidovorax delafieldii, Acidovorax temperans, Burkholderia vietnamiensis, Comamonas thiooxydans, Nitrobacter vulgaris, Nitrobacter winogradskyi, Paracoccus denitrificans, Pseudomonas aeruginosa, Pseudomonas fluorescens, and Thiothrix nivea. Paracoccus denitrificans stands out for having the largest number of complete pathways, possessing the genes of denitrification, dissimilatory nitrate reduction, assimilatory sulfate reduction, and phosphorus accumulation processes. Nitrification pathway was less frequent, found only in 2 species: Candidatus Nitrospira nitrificans and Candidatus Nitrospira nitrosa. Therefore, the results of this work help in understanding the metabolic processes performed by the bacteria in the sewage treatment plants and in optimizing the process that indicate which bacteria are more adapted to bioremediation. In addition, the results can be used in the development of more efficient genetically modified organisms to depollute sewages.